Empowering Health Cadres on Nutrition Education for Pregnant Women in Industrial Areas during the Pandemic - Lasiyati Yuswo Yani; Raras Merbawani; Asef Wildan Munfadlila (Jurnal Ners, 2021)
Introduction: Pregnant women living in industrial areas are exposed to higher levels of toxic substances, pollutants, and other chemicals; this is exacerbated by the pandemic conditions. Improving the nutritional status of pregnant women can be pursued through nutritional education for pregnant women. This study aimed to determine the differences in nutrition fulfilment patterns of pregnant women, before and after nutrition education.Methods: This study used quasi-experimental research with a one group pre post-test design. The samples were 51 pregnant women in industrial areas. Treatment in this study was nutrition education by empowering health cadres. The instrument of this research is an observation sheet that has been tested for validity and reliability. Data analysis used a statistical paired t-test.Results: Knowledge of pregnant women increased by 5.21% after treatment, and behaviour increased by 5.2%. The t-test showed that the the nutrition education model for pregnant women in industrial areas could significantly increase the knowledge (p-value = 0.000) and improve the behaviour (p-value = 0.000) of pregnant women.Conclusion: Nutrition education for pregnant women provided by health cadres is proven to increase knowledge of pregnant women about nutrition and behaviour of fulfilling nutrition during pregnancy in a pandemic situation. During the pandemic, pregnant women can increase knowledge related to nutrition fulfilment through the assistance of health cadres without worrying about being exposed to viruses from care providers.